2005
DOI: 10.1097/00061198-200502000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Needle Revision of Failed Filtering Blebs Using 5- Fluorouracil and a Combined Ab-Externo and Ab-Interno Approach

Abstract: In failed filtering blebs, needle revision with 5-Fluorouracil and a combined ab-externo and ab-interno approach results in high success and low complication rates. The outcome of this procedure compares favorably with previously reported revision techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In some studies, the success rates range from 54% to 84% at 1 year, depending on different definition of success and case selection. 13,14,15,16,17 In the present study, we reported efficacy of this procedure in chronic filtering bleb failure over 6 months after trabeculectomy in Thai eyes with 80.4 % success rate without serious visual threatening complications. We also reported on factors associated with procedural failure.…”
Section: Discussionmentioning
confidence: 65%
“…In some studies, the success rates range from 54% to 84% at 1 year, depending on different definition of success and case selection. 13,14,15,16,17 In the present study, we reported efficacy of this procedure in chronic filtering bleb failure over 6 months after trabeculectomy in Thai eyes with 80.4 % success rate without serious visual threatening complications. We also reported on factors associated with procedural failure.…”
Section: Discussionmentioning
confidence: 65%
“…Mazey et al described reversible corneal edema due to endothelial damage 26. However, the potential for more serious complications, such as kissing choroidal detachment,27 suprachoroidal hemorrhage,8 malignant glaucoma,19 and enodophthalmitis,8 should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, both cornea and sclera are relatively avascular tissues, implying that long-term adhesion of the partial thickness flaps on their underlying beds may be incomplete. The fact that both corneal flap (in LASIK) and partial thickness scleral flap (in trabeculectomy) can be re-raised in cases of revision of the initial procedure further supports this concept [1215]. …”
Section: Discussionmentioning
confidence: 99%